Metode Fashohatul Lisan di Indonesian Al-Qur’an Center untuk Meningkatkan Kualitas Bacaan Al-Qur’an - Apriliani, Rika; Suresman, Edi; Hermawan, Wawan (PT. Student Rihlah Indonesia, 2023)
The background of this research is that the majority of Muslims in Indonesia are still unable to read the Qur’an in accordance with the science of recitation. The purpose of this study is to describe the process of planning, implementing and evaluating fashohatul lisan learning activities at the Indonesian Al-Qur'an Center institution. The research approach used is qualitative with descriptive method. The data analysis technique uses interactive analysis from Miles & Huberman which consists of data reduction, data presentation and conclusion/verification. Data collection techniques used are interviews, observation and documentation. The findings of this study are that the fashohatul lisan method is the basic method of learning the Qur'an at the Indonesian Al-Qur'an Center which focuses on fluency letter by letter in reading the Qur'an, has an urgency as a first step for standardizing recitation in verse until Rasulullah saw. The fashohatul lisan method has an influence on improving the quality of reading the Qur’an, namely the reading of the Qur’an which is standardized according to the reading of the Prophet Muhammad.